2015
DOI: 10.1021/acs.jctc.5b00660
|View full text |Cite
|
Sign up to set email alerts
|

PACSAB: Coarse-Grained Force Field for the Study of Protein–Protein Interactions and Conformational Sampling in Multiprotein Systems

Abstract: Molecular dynamics simulations of proteins are usually performed on a single molecule, and coarse-grained protein models are calibrated using single-molecule simulations, therefore ignoring intermolecular interactions. We present here a new coarse-grained force field for the study of many protein systems. The force field, which is implemented in the context of the discrete molecular dynamics algorithm, is able to reproduce the properties of folded and unfolded proteins, in both isolation, complexed forming wel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
31
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(32 citation statements)
references
References 47 publications
1
31
0
Order By: Relevance
“…In the context of discrete molecular dynamics, a new coarse-grained force field has been recently introduced to investigate PPI and conformational sampling of multiprotein systems. 491 Interestingly, it was also reported that coarsegrained models can accurately reproduce interaction strength for protein complexes of known structure. 492 An interesting example of a coarse-grained approach to protein docking is the ATTRACT model.…”
Section: Protein Interactionsmentioning
confidence: 99%
“…In the context of discrete molecular dynamics, a new coarse-grained force field has been recently introduced to investigate PPI and conformational sampling of multiprotein systems. 491 Interestingly, it was also reported that coarsegrained models can accurately reproduce interaction strength for protein complexes of known structure. 492 An interesting example of a coarse-grained approach to protein docking is the ATTRACT model.…”
Section: Protein Interactionsmentioning
confidence: 99%
“…To avoid being trapped in such minima, the HS--MMC switches between an all--atom Hamiltonian to an excluded volume Hamiltonian to push the IDR away from the ordered domain.Both, MD--based and MC--based approaches may suffer from inaccuracies of current energy models, which are better suited to globular proteins, and tend to provide structurally biased ensembles that do not properly reflect the conformational behaviour in solution of unstructured proteins(Best et al, 2014;Henriques et al, 2015). The development of more suitable force--fields and solvation models for IDPs are key issues for a correct performance of computational methods(Vitalis and Pappu, 2009b;Emperador et al, 2015).Knowledge--based statistical approaches are an alternative to physics--based energy functions. The most representative knowledge--based method for the generation of atomistic models of disordered proteins is Flexible--Meccano (FM)(Bernadó et al, 2005;Ozenne et al, 2012), although other similar methods have been described(Jha et al, 2005).…”
mentioning
confidence: 99%
“…In this work, we apply our PACSAB model [ 9 ] to the study of protein aggregation and protein–protein molecular recognition. The PACSAB model is a coarse-grained protein model based on an implicit solvent approach, which uses a highly detailed coarse-grained representation of the amino acid side chains, while keeping an atomistic representation of the backbone in order to describe accurately secondary structure elements.…”
Section: Introductionmentioning
confidence: 99%